2010
DOI: 10.1111/j.1556-4029.2010.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Statistical Methods for the Determination of Age of Death Using Dental Root Translucency and Periodontosis

Abstract: Lamendin and colleagues (1992) proposed to assess age-at-death from root translucency and periodontosis. Several teeth from the same individual were included in their study. In our work, we evaluate the reliability of their formulas without introducing this bias. Our sample was constituted of 214 individuals (114 males and 100 women) selected from the Terry collection (U.S.A.). The R(2) between age and both indicators is equal to 0.33 and 0.08 (p < 0.001). Based on linear regression, the mean of standard error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
3
6
0
9
Order By: Relevance
“…Just as in the studies conducted by Lamendin , Prince & Ubelaker , and Megyesi , various teeth belonging to the same subject were included. This is a source of bias according to some authors , because it reduces variability within the sample (e.g., some samples may not show independence). Our study has revealed a certain level of variability in each case, even when it involved teeth from the same individual.…”
Section: Resultsmentioning
confidence: 99%
“…Just as in the studies conducted by Lamendin , Prince & Ubelaker , and Megyesi , various teeth belonging to the same subject were included. This is a source of bias according to some authors , because it reduces variability within the sample (e.g., some samples may not show independence). Our study has revealed a certain level of variability in each case, even when it involved teeth from the same individual.…”
Section: Resultsmentioning
confidence: 99%
“…Research on estimation methods for the age of adult skeletons is still a developing area in both fields. It is now well established that inter-individual variability of age-related bone changes are caused by a complex interaction between many factors, and that the observed pattern may be different depending on the population under study [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These collections have mainly been used as a foundation for the development of standardized methods in order to estimate biological characteristics on unknown individuals from their skeletal remains, which is of the utmost importance in both archaeological and forensic contexts (Anderson et al, 2010;Auerbach and Ruff, 2004;Brooks and Suchey, 1990;Loth and Henneberg, 1996;Lovejoy et al, 1985;Schmitt et al, 2010;Steyn andİş can, 1997;Todd, 1920;Trotter and Glaser, 1952;Walker, 2005).…”
mentioning
confidence: 99%